Rapidly enlarging primary cutaneous anaplastic large T-cell lymphoma of the eyelid-A case report - Kumar , Vijay; Ahmed , Nisar; Fatima , Tooba; Khan, Nimra Ahmed (Journal of the Pakistan Medical Association, 2024)
Non-Hodgkin CD30+ T-cell lymphoproliferative disease encompasses three subgroups, one of which is primary cutaneous anaplastic large T-cell lymphoma (PC-ALCL). It is distinguished by the presence of giant anaplastic cells with pleomorphism and widespread CD30 positivity. The case of a 58-year-old female is presented who reported to the Eye Department of Jinnah Post-Graduate Medical Centre (JPMC) on 18th January, 2023 with a three-month history of rapidly enlarging, non-tender, ulcerated lesion on the lower eyelid of the right eye. The histopathology report identified the lesion as CD30+ primary cutaneous anaplastic large cell lymphoma. Computed tomography (CT) scanning of the orbit revealed no extension, and positron emission tomography-computed tomography (PET-CT) showed no systemic involvement. The patient underwent surgical excision without adjuvant chemo-radiation and has remained in clinical remission for five months. Keywords: Eyelid Neoplasm, Anaplastic Large Cell Lymphoma, Eye Cancer, Eyelid Disease.